Penggunaan E-Filing dan Pengetahuan Perpajakan dalam Meningkatkan Kepatuhan Wajib Pajak - Irene Yuliana Sitompul; Ronny Buha Sihotang (Universitas Muhammadiyah Surabaya, 2023)
Abstract Tax is a monetary obligation owed by taxpayers to the government, it is used to fund public needs and wellbeing. Nonetheless, the number of yearly tax returns has not consistently surpassed the goal since some taxpayers fail to make their payments on time. One method the DJP is attempting to promote taxpayer compliance is via tax reform, namely the use of the e-filing system, by optimising services to raise public knowledge of the significance of being an orderly taxpayer. Assessing taxpayers' awareness of taxes and changes to tax laws is done via the use of tax knowledge. This research aimed to ascertain and evaluate how tax knowledge and the e-filing system may be used to enhance taxpayer compliance. At the Adventist University of Indonesia, 60 respondents from the sample were given online questionnaires by researchers using quantitative approaches to gather data. The study's findings, which demonstrate how easy it is for taxpayers to submit their tax responsibilities, demonstrate that e-filing is an effective way to increase taxpayer compliance. Additional findings indicate that taxpayer compliance is impacted by the tax knowledge variable. Keywords: E-filing, tax knowledge, taxpayer compliance